Masculinity and Asian Men’s Health: a Critical Review (International Journal of Nursing Education, 2021)
Literature demonstrated significant consequences to men’s health outcome secondary to their adherenceto certain masculine behaviour and norm. In the West, the norms surrounding masculinity includesthe idea that men should be healthy, strong, and self-sufficient. Western studies revealed that menadherence to this ideology of masculinity reflects their reluctance to seek for health help resulting intheir poor health service utilisation and poor health outcomes. However, it is posited that masculinityis not the declaration of one’s true self, but it is rather socially constructed, rather fluid in its nature andvaries across different context. Therefore, this concept of masculinity needs to be carefully analysedand examine whether it also fits for every man coming from other parts of the world. This paper looksat this issue and questioned its applicability for men living outside the Global North, which has beenoverlooked.